Increasing the appropriate seedling density for higher yield in dry direct-seeded rice sown by a multifunctional seeder after wheat-straw return - Jin-yu TIAN; Shao-ping LI; Shuang CHENG; Qiu-yuan LIU; Lei ZHOU; Yu TAO; Zhi-peng XING; Ya-jie HU; Bao-wei GUO; Hai-yan WEI; Hong-cheng ZHANG (Journal of Integrative Agriculture)
Dry direct-seeded rice (DDR) sown using a multifunctional seeder that performs synchronous rotary tillage and sowing has received increased attention because it is highly efficient, relatively cheap, and environmentally friendly. However, this method of rice production may produce lower yields in a rice–wheat rotation system because of its poor seedling establishment. To address this problem, we performed field experiments to determine the rice yield at five seedling density levels (B1, B2, B3, B4, and B5=100, 190, 280, 370, and 460 seedlings m−2, respectively) and clarify the physiological basis of yield formation. We selected a representative high-quality rice variety and a multifunctional seeder that used in a typical rice–wheat rotation area in 2016 and 2018. The proportion of main stem panicle increased with increasing seedling density. There was a parabolic relationship between yield and seedling density, and the maximum yield (9.34−9.47 t ha−1) was obtained under B3. The maximum yield was associated with a higher total spikelet number m−2 and greater biomass accumulation from heading to maturity. The higher total spikelet number m−2 under B3 was attributed to an increase in panicle number m−2 compared with B1 and B2. Although the panicle numbers also increased under B4 and B5, these increases were insufficient to compensate for the reduced spikelet numbers per panicle. Lower biomass, smaller leaf area, and lower N uptake per plant from the stem elongation stage to the heading stage were partially responsible for the smaller panicle size at higher seedling density levels such as B5. The higher biomass accumulation under B3 was ascribed to the increases in the photosynthetic rate of the top three leaves m−2 of land, crop growth rate, net assimilation rate, and leaf area index. Furthermore, the B3 rice population was marked by a higher grain–leaf ratio, as well as a lower export ratio and transport ratio of biomass per stem-sheath. A quadratic function predicted that 260−290 seedlings m−2 is the optimum seedling density for achieving maximum yield. Together, these results suggested that appropriately increasing the seedling density, and thereby increasing the proportion of panicles formed by the main stem, is an effective approach for obtaining a higher yield in DDR sown using a multifunctional seeder in a rice–wheat rotation system.